Surface expression of major membrane glycoproteins on resting and TRAP-activated neonatal platelets - Simák, J; Holada, K; Janota, J; Stranák, Z (Pediatric research, 1999)
Platelets of full-term newborns and those of healthy adult donors were compared for constitutive expression of surface glycoproteins (GP) Ia-IIa, GP Ib, GP IIb-IIIa, and GP IV and for their activation responses to an agonist by detection of surface expression of activation markers P-selectin and CD63. Resting neonatal platelets showed significantly lower expression of GP Ia-IIa, GP Ib, and GP IIb-IIIa. In contrast, the expression of GP IV was significantly higher compared with platelets of adults. The expression of activation markers P-selectin and CD63 was assessed after in vitro activating of platelets with 0-15 microM human thrombin receptor-activating peptide. At low concentrations of thrombin receptor-activating peptide, the extent of surface expression of activation markers did not differ significantly between adult and neonatal platelets. However, after activation with 15 microM thrombin receptor-activating peptide, the extent of surface expression of P-selectin and CD63 was significantly lower in neonatal platelets. Because of ethical reasons, our study was conducted on neonates with a moderate neonatal hyperbilirubinemia. The remote possibility that hyperbilirubinemia could influence the expression of platelet surface receptors and the reactivity of neonatal platelet cannot be excluded. The role of higher expression of GP IV on neonatal platelets, also seen in certain hematologic malignancies in adults, remains to be elucidated. The lower expression of platelet adhesive receptors and the limited ability to up-regulate granular glycoproteins may play a role in the impairment of function of neonatal platelets.
Keywords: Antigens, CD; novorozenec; Infant, Newborn; integrin alfa2beta1; CD antigeny; techniky in vitro; Humans; Platelet Activation; trombocytový glykoproteinový komplex Ib-IX; dospělí; trombocyty; Platelet Glycoprotein GPIb-IX Complex; P-selektin; trombocytový glykoproteinový komplex IIb-IIIa; lidé; P-Selectin; Adult; Peptide Fragments; Blood Platelets; Integrin alpha2beta1; Platelet Glycoprotein GPIIb-IIIa Complex; aktivace trombocytů; Tetraspanin 30; peptidové fragmenty; In Vitro Techniques; glykoproteiny membrány trombocytů; antigeny CD63; Platelet Membrane Glycoproteins